Resurrection of Oxythyrea abigailoides Mikšić, 1978 (Coleoptera: Scarabaeidae: Cetoniinae) based on new morphological, morphometrical and molecular data - Král, David; Šípek, Petr; Sommer, David; Vondráček, Dominik (Zootaxa, 2023)
Oxythyrea abigailoides Mikšić, 1978, resurrected species, is removed from synonymy with Oxythyrea dulcis Reitter, 1899 and regarded as a separate species. The differential diagnosis of both species is presented on the basis of clearly different morphological, morphometric and molecular characters. Complete chresonomy to both species is given and known geographical distribution to date is summarized and mapped.